Poly[[[μ-trans-1,2-bis(pyridin-4-yl)ethene-κ2N:N′]-μ-iodido-copper(I)]–trans-1,2-bis(pyridin-4-yl)ethene (1/0.25)] - Jessica L. Hoffman; Jessie E. Akhigbe; Eric W. Reinheimer; Bradley W. Smucker (IUCrData, 2020)
The title compound, {[CuI(bpe)]·0.25(bpe)}n, was synthesized similarly to (CuI)2(bpe) [Neal et al. (2019). IUCrData, 4, x190122] with red crystals grown from acetonitrile solutions of CuI and the bpe ligand [bpe = 1,2-bis(pyridin-4-yl)ethene, C12H10N2]. The structure of the title compound is a type 1 complex in the Graham nomenclature [Graham et al. (2000). Inorg. Chem. 39, 5121–5132], having rhombic dimers of Cu2I2 that are bridged by two bpe ligands, to form oligomeric ribbons arranged as stairsteps. The step height is 2.8072 (11) Å, which is the Cu—Ii distance of the dimer [symmetry code (i): 1 − x, 2 − y, 1 − z]. The resulting polymer displays a two-dimensional honeycomb framework along the (01\overline1) plane, and disordered free bpe molecules fill the voids in the crystal.